Microdissection oncoTESE (micro-oncoTESE) in azoospermic men with suspected testicular cancer: Analysis of outcomes from a specialist centre. (July 2022) - Kaul, Asheesh; Katelaris, Athos; Haider, Aiman; Freeman, Alex; Ahmed, Kamran; Alnajjar, Hussain M; Muneer, Asif
Objective: The main aim of this study was to report the outcomes of azoospermic men with suspicious testicular lesions, undergoing microsurgical sperm retrieval (micro-oncoTESE) at the time of radical/partial orchidectomy. Patients and methods: Testicular lesions suspicious for cancer were confirmed on ultrasound scanning. In patients undergoing radical inguinal orchidectomy, ex vivo microdissection of the unaffected testicular parenchyma was performed. Microdissection was performed in vivo for partial orchidectomy. The primary outcome measure was surgical sperm retrieval (SSR) rate. Results: A total of 33 patients (median age 33 years, interquartile range (IQR) 22) with suspected testicular cancer (TCa) underwent micro-oncoTESE. Histological analysis confirmed TCa in 26 patients and benign pathology in 7 patients. The overall SSR rate was 39%. Sub-analysis of patients with TCa and benign histology found that the SSR was 46% and 14%, respectively. There was no significant difference in maximum tumour length between successful and unsuccessful SSR groups 33.9 mm ± 23 (SD) versus 29.8 mm ± 17.5 (SD) ( p  = 0.62). Conclusion: Based on our cohort, micro-oncoTESE provides an option for sperm retrieval in azoospermic men with testicular lesions.